Understanding Corrosion Morphology of Duplex Stainless Steel Wire in Chloride Electrolyte - Örnek, Cem; Davut, Kemal; Kocabaş, Mustafa; Bayatlı, Aleyna; Ürgen, Mustafa (MDPI AG, 2021)
The corrosion morphology in grade 2205 duplex stainless steel wire has been studied to understand the nature of pitting and the causes of the ferrite phase's selective corrosion in acidic NaCl solution. It is shown that the corrosion mechanism is always pitting, which either manifests lacy cover perforation or densely-arrayed selective cavities developing on the ferrite phase. Pits with a lacy metal cover form in concentrated chloride solutions, whereas the ferrite phase's selective corrosion develops in diluted electrolytes, showing dependency on the chloride-ion concentration. The pit perforation is probabilistic and occurs on both austenite and ferrite grains. The lacy metal covers collapse in concentrated solutions but remain intact in diluted electrolytes. The collapse of the lacy metal cover happens due to hydrogen embrittlement. Pit evolution is deterministic and occurs selectively in the ferrite phase in light chloride solutions.
Keywords: electron backscattered diffraction; selective corrosion; potentiodynamic polarisation; corrosion morphology; Chemical technology; pitting corrosion; wire; TP1-1185; materials_science_other; hydrogen embrittlement; duplex stainless steel; lacy cover pit perforation; scanning electron microscopy